The aetiology of extreme tall stature in a screened Finnish paediatric population. (December 2021) - Kärkinen, Juho; Sorakunnas, Eero; Miettinen, Päivi J.; Raivio, Taneli; Hero, Matti
ABSTRACT: Background: Extremely tall children (defined as height SDS (HSDS) ≥+3) are frequently referred to specialized healthcare for diagnostic work-up. However, no systematic studies focusing on such children currently exist. We investigated the aetiology, clinical features, and auxological clues indicative of syndromic tall stature in extremely tall children subject to population-wide growth monitoring and screening rules. Methods: Subjects with HSDS ≥+3 after three years of age born between 1990 and 2010 were identified from the Helsinki University Hospital district growth database. We comprehensively reviewed their medical records up to December 2020 and recorded underlying diagnoses, auxological data, and clinical features. Findings: We identified 424 subjects (214 girls and 210 boys) who fulfilled the inclusion criteria. Underlying growth disorder was diagnosed in 61 (14%) patients, in 36 (17%) girls and 25 (12%) boys, respectively (P=015). Secondary causes were diagnosed in 42 (10%) patients and the two most frequent secondary diagnoses, premature adrenarche, and central precocious puberty were more frequent in girls. Primary disorder, mainly Marfan or Sotos syndrome, was diagnosed in 19 (4%) patients. Molecular genetic studies were used as a part of diagnostic work-up in 120 subjects. However, array CGH or next-generation sequencing studies were seldom used. Idiopathic tall stature (ITS) was diagnosed in 363 (86%) subjects, and it was considered familial in two-thirds. Dysmorphic features or a neurodevelopmental disorder were recorded in 104 (29%) children with ITS. The probability of a monogenic primary growth disorder increased with the degree of tall stature and deviation from target height. Interpretation: A considerable proportion of extremely tall children have an underlying primary or secondary growth disorder, and their risk is associated with auxological parameters. Clinical features related to syndromic tall stature were surprisingly frequent in subjects with ITS, supporting the view that syndromic growth disorders with mild phenotypes may be underdiagnosed in extremely tall children. Our results lend support to comprehensive diagnostic work-up of extremely tall children. Funding: Päivikki and Sakari Sohlberg Foundation, Foundation for Pediatric Research, and Helsinki University Hospital research grants.